(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines how artificial intelligence and financial technology are reshaping modern law across public regulation, private law, and procedural justice. The core claim is that AI and FinTech do not merely introduce new products and services. They alter institutional roles, redefine legal categories, and compress the time between innovation and harm, forcing legal systems to move from episodic rulemaking toward continuous governance. The article develops a conceptual framework that links technological capabilities to legal functions, then maps concrete pathways of legal change in financial regulation, consumer protection, competition law, data governance, cybersecurity, anti money laundering, and dispute resolution. Comparative attention is given to the European Union’s risk based approach to AI and its operational resilience regime for finance, the evolving international standards on virtual assets, and the emerging policy architecture in developing jurisdictions. The article argues that the most durable legal responses combine three elements: ex ante obligations for high impact uses, measurable accountability tools such as auditability and incident reporting, and procedural safeguards that protect due process when automated systems affect rights and access to essential services. The conclusion proposes a set of legally implementable design principles for regulators, courts, and market actors, emphasizing proportionality, transparency, contestability, and resilience as the shared grammar of future legal development.